Comprehensive Review of Health Security, Social Work Integration, and Health Assistants in Strengthening Community Healthcare Systems - Almansour, Fahad Obyan Saleh; Al Mutarid, Hassan Hamad Binali; Alsalem, Ibrahim Ahmed Abdullah; Almanssor, Mani Hamad Ali; Lsalumi, Mesfer Salem Bin Jaber; Almansour, Obeed Hashan Rashed; Lasloum, Al-Hassan Hadi Saleh; Al mansour, Hussain Mohameed masoud; Alyami, Ali Salem Saleh; Almutlaq, Refan Nasser Mubarak (Journal of Ecohumanism, 2024)
This review looks at the involvement of health security measures and the incorporation of social workers and health assistants in community healthcare organizations. It looks at the synergistic effects that exist when implementing those approaches in enhancing accessibility, efficiency, and general health status. Several cases from around the world are examined to demonstrate how interdisciplinary solutions can be used to build resilience in communities. The research evidence unveils ways of enhancing investment in social work and health assistants for an improved delivery of resource-efficient and patient-focused care. Suggestions for future frameworks are presented.